Bovine oocyte competence shows better tolerance to seasonal cold stress in cold areas of Northern China. (3rd April 2017) - Guo, Z. H.; He, X. M.; Liu, D.; Ma, H.; Zhang, D. F.; Wu, H. D.; Wu, S. H.; Li, Z. Q.; Fu, B.; Wang, J. B.; Wang, L.; Liu, Z. G.; et al.
ABSTRACT: Oocyte competence is an important determinant of reproductive success and can be disrupted by heat/cold stress. Information related to seasonally induced cold stress effects in cold areas on oocyte competence in the bovine is still scarce, however. Therefore, we performed experiments to test the hypothesis that seasonally induced cold/heat stress affects bovine oocyte competence in cold areas. Oocytes were collected in the winter, summer, and autumn, and we showed a significantly better survival and growth rate in the cold compared with hot temperatures, as recorded for two-cell and blastocyst stage embryos ( P  < .05). As we intend to perform in vitro fertilization-embryo transfer in winter, we observed a satisfactory level of pregnancy and birth rates during this time period, even when compared with other studies in cold and hot weather ( P  < .05). Therefore, our results suggest that oocyte competence is not affected by cold stress.